Study on Nonfarm Livelihoods in Refugee-Hosting Regions in Ethiopia : Nonfarm Livelihood Subcomponent Assessment and Recommendations for DRDIP Phase II - World Bank (Washington, DC, 2022)
The Development Response to Displacement Impacts Project (DRDIP) is a World Bank-supported regional program in the Horn of Africa (Ethiopia, Uganda, Djibouti, and Kenya), which aims to improve access to social services, expand economic opportunities, and enhance environmental management for host and forcibly displaced communities. It was initiated in 2016 for a five-year period with hundred million US dollars total funding for Ethiopia provided by the government of Ethiopia and the World Bank. For Phase II, DRDIP aims to improve and strengthen the nonfarm livelihood interventions, focusing on women and youth. This study assesses the activities implemented under DRDIP’s nonfarm livelihood subcomponent and provides an analysis of the nonfarm economy in Ethiopia’s refugee-hosting areas to shape future DRDIP interventions. Promising nonfarm livelihood options for refugee and host communities, particularly women and youth, are identified. The study findings offer actionable recommendations with clearly identified entry points for increasing the effectiveness and impact of DRDIP’s nonfarm livelihood activities on the targeted refugees and host communities.